Beclin-1-Dependent Autophagy Protects the Heart During Sepsis. Issue 20 (13th November 2018) - Sun, Yuxiao; Yao, Xiao; Zhang, Qing-Jun; Zhu, Min; Liu, Zhi-Ping; Ci, Bo; Xie, Yang; Carlson, Deborah; Rothermel, Beverly A.; Sun, Yuxiang; Levine, Beth; Hill, Joseph A.; et al.
Abstract : Background: Cardiac dysfunction is a major component of sepsis-induced multiorgan failure in critical care units. Changes in cardiac autophagy and its role during sepsis pathogenesis have not been clearly defined. Targeted autophagy-based therapeutic approaches for sepsis are not yet developed. Methods: Beclin-1-dependent autophagy in the heart during sepsis and the potential therapeutic benefit of targeting this pathway were investigated in a mouse model of lipopolysaccharide (LPS)-induced sepsis. Results: LPS induced a dose-dependent increase in autophagy at low doses, followed by a decline that was in conjunction with mammalian target of rapamycin activation at high doses. Cardiac-specific overexpression of Beclin-1 promoted autophagy, suppressed mammalian target of rapamycin signaling, improved cardiac function, and alleviated inflammation and fibrosis after LPS challenge. Haplosufficiency for beclin 1 resulted in opposite effects. Beclin-1 also protected mitochondria, reduced the release of mitochondrial danger-associated molecular patterns, and promoted mitophagy via PTEN-induced putative kinase 1-Parkin but not adaptor proteins in response to LPS. Injection of a cell-permeable Tat-Beclin-1 peptide to activate autophagy improved cardiac function, attenuated inflammation, and rescued the phenotypes caused by beclin 1 deficiency in LPS-challenged mice. Conclusions: These results suggest that Beclin-1 protects the heart during sepsis and that the targeted induction of Beclin-1 signaling may have important therapeutic potential. Abstract : Supplemental Digital Content is available in the text.